2016
DOI: 10.1038/srep37751
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin attenuates cigarette smoke extract-induced inflammation via simultaneous inhibition of autophagy and ERK/p38 MAPK pathway in human bronchial epithelial cells

Abstract: Cigarette smoke (CS) is a major risk of chronic obstructive pulmonary disease (COPD), contributing to airway inflammation. Our previous study revealed that silymarin had an anti-inflammatory effect in CS-exposed mice. In this study, we attempt to further elucidate the molecular mechanisms of silymarin in CS extract (CSE)-induced inflammation using human bronchial epithelial cells. Silymarin significantly suppressed autophagy activation and the activity of ERK/p38 mitogen-activated protein kinase (MAPK) pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 57 publications
(62 reference statements)
4
65
0
Order By: Relevance
“…Activation of ERK1/2 subsequently triggers phosphorylation of a number of downstream targets that regulate the autophagy pathway. ERK1/2 phosphorylation has been shown to enhance autophagy in Silymarin-treated Beas-2B cells or mediate phosphorylated Bcl-2 regulated starvation-induced autophagy (Tang et al, 2010;Li et al, 2016). It has been shown that MEK-ERK inhibitors, such as U0126, or amino acids can inhibit autophagy (Pattingre et al, 2003;Tang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2 subsequently triggers phosphorylation of a number of downstream targets that regulate the autophagy pathway. ERK1/2 phosphorylation has been shown to enhance autophagy in Silymarin-treated Beas-2B cells or mediate phosphorylated Bcl-2 regulated starvation-induced autophagy (Tang et al, 2010;Li et al, 2016). It has been shown that MEK-ERK inhibitors, such as U0126, or amino acids can inhibit autophagy (Pattingre et al, 2003;Tang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…() showed that CSE‐induced apoptosis in BEAS‐2B cells was regulated by the ASK‐1/p38 signalling cascade. Another study on BEAS‐2B cells showed that CSE‐induced upregulation of inflammatory cytokines was dependent on the ERK/p38 signalling pathway (Li D et al., ). In contrast to these studies, Li, Xu, and Shen () demonstrated that CSE does not activate MAPKs and does not affect the release of IL‐8 in primary epithelial cells of the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2014) showed that CSE-induced apoptosis in BEAS-2B cells was regulated by the ASK-1/p38 signalling cascade. Another study on BEAS-2B cells showed that CSE-induced upregulation of inflammatory cytokines was dependent on the ERK/p38 signalling pathway (Li D et al, 2016). In contrast to these studies, Li, Xu, and Shen (2007) Induction of apoptosis through the activation of FasL-p38/JNK-Jun signalling pathway in lungs of smoking rats was demonstrated (Kuo et al, 2005;Wu, Lin, Yan, Wu, & Wang, 2006).…”
Section: Activation Of Mapks By Csementioning
confidence: 92%
“…For example, in a previous study published by our group, we found that the levels of pulmonary autophagy in a COPD mouse model were increased, and that the levels of inflammatory cytokines in bronchoalveolar lavage (BAL) fluid were also increased [27]. In another study, Li and co-workers found that silymarin reduced airway inflammation induced by cigarette smoke by inhibiting autophagy and the ERK/p38 MAPK pathway [28].…”
Section: Introductionmentioning
confidence: 91%